Adverse childhood experiences, associated stressors and comorbidities in children and youth with fetal alcohol spectrum disorder across the justice and child protection settings in Western Australia - Grace Kuen Yee Tan; Martyn Symons; James Fitzpatrick; Sophia G. Connor; Donna Cross; Carmela F. Pestell (BMC, 2022)
Abstract Background Individuals with Fetal Alcohol Spectrum Disorder (FASD) are at risk of having adverse childhood experiences (ACEs), especially those with child protection and/or justice system involvement. The complex relationship between FASD and psychosocial vulnerabilities in the affected individual is an important clinical risk factor for comorbidity. This study (1) explored the ACEs and associated stressors in individuals with FASD; (2) investigated the association between ACEs and negative outcomes, i.e., justice/child protection system involvement; and (3) examined the relationship between ACEs and comorbid conditions such as mood and neurodevelopmental disorders. Methods Data were collected retrospectively via file review from diagnostic clinics in Western Australia. Life adversity was coded using a standardised ACEs questionnaire. A total of 211 participants (72% males) with FASD with a mean age of 11 years (range = 2-21) were included in the final sample. 70% of the total sample had been involved with the child protection system and 40% had trouble with the law. Results Exposure to drinking/substance misuse at home (70%) and domestic violence (52%) were the two most common ACEs across the total sample. In the entire cohort, 39% had four or more ACEs, indicating higher risks of poor health outcomes. Additional stressors recorded were disengagement from school (43%), transiency (19%), victims of bullying (12%), traumatic brain injury (9%) and homelessness (5%). ACEs such as drinking/substance misuse at home, emotional neglect and physical neglect were positively associated with child protection system involvement. Additionally, exposure to domestic violence was positively correlated with justice system involvement. Higher rates of life adversity in this clinical population were associated with an increased number of comorbidities. Specifically, those with FASD who had comorbidities such as attachment disorder, substance use disorder, and PTSD also reported higher ACEs scores. Conclusion ACEs were common in this clinical population. Increased ACEs in this sample were associated with increased comorbidities and involvement with the child protection and/or justice system. This highlights that prevention, intervention and early diagnosis of FASD are important for at risk children to reduce the negative effects of ACEs.